Роль иммунологических факторов инвазивности в патогенезе генитального эндометриоза - Потапова, Лілія Вікторівна; Потапова, Лилия Викторовна; Potapova, Liliia; Ліпко, Оксана Петрівна; Липко, Оксана Петровна; Lipko, Oksana; Мерцалова, Ольга Владиславівна; Мерцалова, Ольга Владиславовна; Mertsalova, Olga; Чехунова, Анастасія Олександрівна; Чехунова, Анастасия Александровна; Chekhunova, Anastasiia (Харьковская медицинская академия последипломного образования, 2018)
This paper presents new factors of immunopathogenesis of endometriosis. Ectopic endometrial growth is determined by impaired tissue resistance as the result of the development of destructive-degener- ative processes in it. The development of endometriosis occurs under both high expression of metal- loproteinases, which causes remodeling of the stroma, and adhesins in the tissues of the peritoneum.
Keywords: endometriosis; adhesion molecules; metalloproteinases; invasiveness